2015
DOI: 10.1017/s1041610215000691
|View full text |Cite
|
Sign up to set email alerts
|

A systematic narrative review of support groups for people with dementia

Abstract: Although qualitative studies will remain important in this area, further mixed-methods randomized controlled trials (RCTs)or comparison group studies with longer follow-up periods are needed to strengthen the evidence base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Söderhamn et al 2014Clare et al 2008Leung et al 2015;Toms et al 2015;Keyes et al 2016 Planning ahead for future impact of the condition with the aim of increased sense of control. Robinson et al 2015;Grand et al 2011;SCIE, 2015; Alzheimer's Association; Hellström & Torres, 2016 Adapting activity to capability Adapting capability to activity (and goals of activities), in order to feel that activities are manageable and successful.…”
Section: Methodsmentioning
confidence: 99%
“…Söderhamn et al 2014Clare et al 2008Leung et al 2015;Toms et al 2015;Keyes et al 2016 Planning ahead for future impact of the condition with the aim of increased sense of control. Robinson et al 2015;Grand et al 2011;SCIE, 2015; Alzheimer's Association; Hellström & Torres, 2016 Adapting activity to capability Adapting capability to activity (and goals of activities), in order to feel that activities are manageable and successful.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it has been reported that a support group for people with dementia in the early stage held once a week for 9 consecutive weeks showed positive effects on people with dementia, but not on family members [21]. Since the primary aim of the present study was to analyze a dementia café which would improve the QOL of people with dementia and their families, studies of psychosocial interventions and support groups would be helpful in terms of the setting parameters [22][23][24][25]. However, caution is required because dementia cafés are typically places where people with dementia and their families come together, along with others in the community.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, the literature on support groups for people with dementia has also been reviewed recently by Toms et al . () and by Leung et al . ().…”
Section: Methodsmentioning
confidence: 97%
“…For repeated measures studies, we followed the procedure adopted by Toms et al . () and rated studies in terms of the relevant 28 CONSORT items (Moher et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation